ANALISIS PENGARUH PENGELUARAN PEMERINTAH DAN PENDAPATAN PERKAPITA TERHADAP INDEKS PEMBANGUNAN MANUSIA DAN PERTUMBUHAN EKONOMI DI SULAWESI SELATAN - Herdial, Herdial; Rizka, Jafar (ICOR: Journal of Regional Economics, 2022)
Economic growth requires a strong commitment from the government and the private sector. This study aims to analyze the effect of government spending and per capita income on the human development index and economic growth in South Sulawesi Province in 2011-2021. This study concludes that government spending and income per capita from 2011-2021 have a positive and significant impact on economic growth and Human Development Index in South Sulawesi Province. Besides that, government spending has a positive but not significant effect on the Human Development Index in South Sulawesi Province. Lastly, it is found that government spending and income per capita have a direct and indirect significant influence on the Human Development Index and economic growth. Keywords: Government Spending, Income Per Capita, Human Development Index. Economic Growth